2021
DOI: 10.1016/j.immuni.2021.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide controls proliferation of Leishmania major by inhibiting the recruitment of permissive host cells

Abstract: Summary Nitric oxide (NO) is an important antimicrobial effector but also prevents unnecessary tissue damage by shutting down the recruitment of monocyte-derived phagocytes. Intracellular pathogens such as Leishmania major can hijack these cells as a niche for replication. Thus, NO might exert containment by restricting the availability of the cellular niche required for efficient pathogen proliferation. However, such indirect modes of action remain to be established. By combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 69 publications
1
18
1
2
Order By: Relevance
“…While the importance of macrophages as host cells for parasites and effector cells involved in parasite killing has been well-characterized, emerging evidence suggests Ly6C + CCR2 + inflammatory monocytes are a preferential target for parasites and serve as the initial myeloid host cell for early parasite replication; however, monocytes also perform effector functions by producing inducible nitric oxide (iNOS) in an IFNγ-dependent manner to kill parasites [14,[16][17][18][19]. In addition to the parasite taking advantage of the Th1-mediated recruitment of inflammatory monocytes for infection, recruited neutrophils and monocyte-derived dendritic cells at the site of infection can also harbor parasites, suggesting these immune cells serve an important function in host-parasite interplay [16,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the importance of macrophages as host cells for parasites and effector cells involved in parasite killing has been well-characterized, emerging evidence suggests Ly6C + CCR2 + inflammatory monocytes are a preferential target for parasites and serve as the initial myeloid host cell for early parasite replication; however, monocytes also perform effector functions by producing inducible nitric oxide (iNOS) in an IFNγ-dependent manner to kill parasites [14,[16][17][18][19]. In addition to the parasite taking advantage of the Th1-mediated recruitment of inflammatory monocytes for infection, recruited neutrophils and monocyte-derived dendritic cells at the site of infection can also harbor parasites, suggesting these immune cells serve an important function in host-parasite interplay [16,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Leishmania parasites possess a variety of virulence mechanisms [27,28] and use several strategies to evade the host immune response for intracellular survival including modulating the host immune response by altering T cell responses, impeding antigen display by MHCII, and hindering nitric oxide (NO) production [29,30]. NO not only directly kills parasites, but NO also regulates the breadth of the inflammatory response through quorum sensing and restricts the supply of proliferation-permissive host cells including monocyte-derived phagocytes to the site of infection [26,31,32]. Importantly, Leishmania parasites can escape from oxidative burst and they fail to activate optimal macrophage innate immune responses [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the contribution of monocytes to the maintenance of dermal macrophages at later time points (after more than 1 month) cannot be completely excluded, as experiments using BM chimeras showed approximately 25% contribution of BM-derived donor cells to the dermal macrophage compartment at 16 weeks [ 20 ]. Finally, a recent publication using another strain of L. major demonstrated that parasite replication in self-contained infection was limited by decreased monocyte recruitment due to NO [ 49 ]. The association of enhanced monocyte accumulation in the periphery and increased numbers of myeloid progenitor cells with persistent infection in our study further suggests that monocytes contribute to parasite replication in cutaneous leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Leishmania infection, it is tempting to speculate that buffering might increase local NO production in leishmanial lesions. This could enhance direct leishmanicidal activity ( 22 ) and, in addition, might inhibit the excess influx of mononuclear cells, which in turn serve as cellular niches for Leishmania replication ( 25 ). Whether bicarbonate and/or Arg-HCl treatment are useful for this purpose will require additional experimentation, which, for instance, may include monitoring of lesional pH, tissue NO levels and parasite burden.…”
Section: Discussionmentioning
confidence: 99%
“…Control of L. major in this model critically depends on the ability of macrophages to produce high levels of leishmanicidal nitric oxide [NO; reviewed in: ( 18 20 )]. The production of NO during cutaneous L. major infection not only ensures direct killing of the protozoan parasite [reviewed in: ( 21 – 23 )], but NO also curtails the parasite’s metabolic activity ( 24 ) Moreover, NO impairs the recruitment of monocyte-derived phagocytes to the infectious lesions ( 25 ). This mechanism significantly contributes to antimicrobial control as recruited monocyte-derived phagocytes provide an important cellular niche that favor Leishmania replication ( 25 27 ).…”
Section: Introductionmentioning
confidence: 99%